Analisis Perawatan Mesin Boiler Kapasitas 21 Ton/Jam Menggunakan Metode Overall Equipment Effectiveness (OEE) Pada PT XYZ - Muhammad Rizqi Fauzi; Arif, Saiful; Hendarti, Devina Rosa (Jurnal Teknik Terapan, 2025)
This research aims to analyze the performance and maintenance of the 21-ton/hour capacity boiler at PT XYZ through the application of the Overall Equipment Effectiveness (OEE) method. The boiler machine plays a crucial role in the production process, but it often experiences performance degradation that can disrupt the smooth operation of the company. OEE is used to measure how well the machine operates based on three main aspects: availability, performance, and quality. In addition, this study also uses the Six Big Losses analysis to identify the main causes of performance losses in the machine. The data used includes operational time, downtime, and the product quality of the boiler machine from January to December 2024. The analysis results show that the average OEE value of the boiler machine at PT XYZ reaches 93.49%, with an average availability value of 96.37%, performance value of 97.07%, and quality value of 100%. However, the main issues found are losses due to sudden breakdowns (breakdown losses) of 3.64% and reduced speed losses of 1.18%. The performance decline is mostly caused by issues with fuel and combustion. Therefore, it is recommended to conduct more routine fuel testing and improve the combustion process to reduce soot formation and maintain machine stability. This research is expected to assist PT XYZ in improving boiler machine performance and the smooth operation of production.